(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The history of Indian Freedom Struggle would be incomplete without mentioning the contributions of women. The sacrifice made by the women of India will occupy the foremost place. They fought with true spirit and undaunted courage and faced various tortures, exploitations and hardships to earn us freedom.When most of the men freedom fighters were in prison the women came forward and took charge of the struggle. The list of great women whose names have gone down in history for their dedication and undying devotion to the service of India is a long one.Woman’s participation in India’s freedom struggle began as early as in1817 .Bhima Bai Holkar fought bravely against the British colonel Malcolm and defeated him in guerilla warfare. Many women including Rani Channama of Kittur, Rani Begam Hazrat Mahal of Avadh fought against British East India company in the 19th century 30 years before the “First War of Independence 1857”